2012
DOI: 10.1212/wnl.0b013e31826958d3
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural management of acute ischemic stroke intervention

Abstract: Periprocedural medical management is an important aspect in optimizing the outcome of patients who undergo endovascular treatment for acute ischemic stroke. Blood pressure, fluid hydration, and antithrombotics are some of the elements that need to be tailored carefully to the patient according to the patency of his or her cerebral vasculature, the extent of his or her infarct, and the potential for hemorrhagic transformation. This article reviews the medical care of acute stroke patients before and after endov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 85 publications
(68 reference statements)
0
11
0
1
Order By: Relevance
“…Conversely, permissive hypertension may be beneficial in patients with non-recanalized LVO (nrLVO) by maintaining adequate brain perfusion pressure 12. Additionally, aggressive BP reduction in the first 24 hours of ictus has been associated with poor outcomes 15.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, permissive hypertension may be beneficial in patients with non-recanalized LVO (nrLVO) by maintaining adequate brain perfusion pressure 12. Additionally, aggressive BP reduction in the first 24 hours of ictus has been associated with poor outcomes 15.…”
Section: Introductionmentioning
confidence: 99%
“…A U-shaped relationship between BP and functional outcome in patients treated with EVT has been reported [20,21]. Aggressive BP reduction in the first 24 h after EVT has been associated with poor outcomes [21], and in order to maintain adequate brain perfusion pressure, permissive hypertension may be beneficial in nonrecanalized patients [22]. In 2016, a cohort study of 255 patients with severe traumatic brain injuries showed that the rate of poor prognosis was higher in the MCA blood flow deceleration group (MFV <35 cm/s; EDV < 20 cm/s; PI > 1.4 shown by TCD) than in the normal MCA blood flow group (100.0 vs. 19.3%, p = 0.000) [23].…”
Section: Raising Bp Under Tcd Monitoringmentioning
confidence: 99%
“…Verglichen mit der Vielzahl der Studien, die sich mit der präinterventionellen Patientenselektion unter Einsatz der modernen Bildgebung und den Rekanalisationstechniken beschäftigen, ist die Literatur über das periprozedurale Management der Patienten, die für eine endovaskuläre lokale Behandlung infrage kommen, eher übersichtlich [10].…”
Section: Periprozedurales Managementunclassified